Ethnobotanical note, total phenolic content, total flavonoid content, and antioxidative activities of wild edible vegetable, crassocephalum crepidioides from Kota Belud, Sabah - Fadzilah Awang-Kanak; Mohd Fadzelly Abu Bakar; Maryati Mohamed (IOP Publishing Ltd, 2019)
Crassocephalum crepidioides or locally known as “tanduk manggarang” (Bajau) or “gipun” (Dusun) is an underutilized weed that has been consumed as wild edible vegetable by Sama Bajau people in Kota Belud, Sabah. The villagers obtained the plant from local traders at fresh market or foraging the plant from forest. Correlation between TPC and TFC with IC50 of DPPH and ABTS scavenging activities were analysed by using Pearson’s correlation. The ethanolic extract exhibited the highest TPC (175.06±0.574 μg/ml) and TFC (139.72±0.923 μg/ml), followed by hot water extract with TPC of 54.45±0.818 μg/ml and TFC of 25.07±0.156 μg/ml. The distilled water extract showed the lowest TPC (29.98±0.918 μg/ml) and TFC (19.96±0.538 μg/ml). Antioxidant activities also demonstrated the same trend, ethanolic extract displayed the highest percentage of antioxidant activity of DPPH (85.4±1.64 %) and ABTS (85.2±0.57 %), followed by hot water extract with 65.4±3.87 % for DPPH and 79.4±3.2 % for ABTS. Distilled water extract had the lowest antioxidant activities for both DPPH (55.0±0.7 2%) and ABTS (71.35±2.61 %). The IC50 of DPPH assay were decreasing in the subsequent order; distilled water>hot water>ethanolic. Meanwhile, the IC50 of ABTS were decreasing in the following order; hot water>distilled water>ethanolic. There was negative high correlation between TPC in C. crepidioides leaves extracts with their IC50 of DPPH and ABTS assays. Following the same trend, there was also negative high correlation between TFC in C. crepidoides leaves extracts with their IC50 of DPPH and ABTS assays. As a conclusion, this readily available wild edible vegetable could be a potent resource of natural antioxidant for rural populace in Sabah, Malaysian Borneo.